Mid-infrared imaging of Supernova 1987A. Issue 3 (21st October 2022) - Matsuura, Mikako; Wesson, Roger; Arendt, Richard G; Dwek, Eli; De Buizer, James M; Danziger, John; Bouchet, Patrice; Barlow, M J; Cigan, Phil; Gomez, Haley L; Rho, Jeonghee; Meixner, Margaret
ABSTRACT: At a distance of 50 kpc, Supernova 1987A is an ideal target to study how a young supernova (SN) evolves in time. Its equatorial ring, filled with material expelled from the progenitor star about 20 000 yr ago, has been engulfed with SN blast waves. Shocks heat dust grains in the ring, emitting their energy at mid-infrared (IR) wavelengths We present ground-based 10–18 μm monitoring of the ring of SN 1987A from day 6067 to 12814 at a resolution of 0.5 arcsec, together with SOFIA photometry at 10–30 μm. The IR images in the 2000's (day 6067–7242) showed that the shocks first began brightening the east side of the ring. Later, our mid-IR images from 2017 to 2022 (day 10952–12714) show that dust emission is now fading in the east, while it has brightened on the west side of the ring. Because dust grains are heated in the shocked plasma, which can emit X-rays, the IR and X-ray brightness ratio represent shock diagnostics. Until 2007 the IR to X-ray brightness ratio remained constant over time, and during this time shocks seemed to be largely influencing the east side of the ring. However, since then, the IR to X-ray ratio has been declining, due to increased X-ray brightness. Whether the declining IR brightness is because of dust grains being destroyed or being cooled in the post-shock regions will require more detailed modelling.